Association between serum levels of homocysteine with characteristics of migraine attacks in migraine with aura - Omid Sadeghi; Zahra Maghsoudi; Gholamreza Askari; Fariborz Khorvash; Awat Feizi (Journal of Research in Medical Sciences, 2014)
Background: Evidences have shown that migraine with aura (MA) is associated with elevated homocysteine levels but, few studies have evaluated the relationship between homocysteine levels and characteristics of migraine attacks such as severity, frequency, duration and headache diary result (HDR). Thus, in this study, we investigated the association between homocysteine levels and characteristics of migraine attacks in patients with MA. Materials and Methods: This cross-sectional study was carried out in Isfahan city, Iran, in February 2013. Fasting serum levels of homocysteine were measured in 130 MA patients (31 males and 99 females) aged 15-60 years. Severity, frequency and duration of migraine attacks, as well as HDR, were determined in each patient according to international headache society criteria by a neurologist. Linear and ordinal logistic regression tests were used to evaluate the relationship between serum homocysteine levels and characteristics of migraine attacks. Results: There is no significant association between serum levels of homocysteine with severity, frequency, duration and HDR. This association was not significant after adjustment of confounding variables such as age, body mass index (BMI) and family history of migraine. However, serum homocysteine levels were significantly associated with HDR among males after adjustment for age, BMI and family history of migraine (P = 0.01). Conclusion: Significant relationship between homocysteine levels and characteristics of migraine attacks such as severity, frequency, duration and HDR were not found. However, after adjustment of confounding variables, we found a significant positive relationship between homocysteine levels and HDR among men.